The Symbiotic Continuum Within Ticks: Opportunities for Disease Control - Hussain, Sabir; Perveen, Nighat; Hussain, Abrar; Song, Baolin; Aziz, Muhammad Umair; Zeb, Jehan; Li, Jun; George, David; Cabezas-Cruz, Alejandro; Sparagano, Olivier (Frontiers in Microbiology, 2022)
Among blood-sucking arthropods, ticks are recognized as being of prime global importance because of their role as vectors of pathogens affecting humans and other animals. Ticks carry a variety of pathogenic, commensal and symbiotic microorganisms. For the latter, studies are available concerning the detection of tick-borne endosymbionts, but their role in the physiology and ecology of ticks remains largely unexplored. This review paper focuses on major tick endosymbionts, including Coxiella, Rickettsia, Francisella, and Wolbachia-like endosymbionts, and their impact on ticks and the host-parasite relationships that drive disease risk. Symbionts from Rickettsia sp. appear more common in ticks of the genera of Ixodes, Amblyomma and Dermacentor with low probability for their existence in Rhipicephalus, Haemaphysalis and Hyalomma ticks. American dog ticks showed greater motility when infected with Rickettsia, indirectly influencing infection risk, providing evidence of a relationship between tick endosymbionts and tick-vectored pathogens. Widespread occurrence of endosymbionts suggests that their influence on ticks is likely to be significant, with Coxiella-like endosymbionts infecting more than 60% of tick species. Francisella-like endosymbionts have been identified in tick genera such as Dermacentor, Amblyomma, Ornithodoris, Ixodes, and Hyalomma, whereas Wolbachia sp. have been detected in Ixodes, Amblyomma, Hyalomma and Rhipicephalus tick genera. We currently understand relatively little on how these endosymbionts influence tick parasitism, vector capacity, pathogen transmission and colonization, and ultimately on how they influence tick-borne disease dynamics. Filling this knowledge gap represents a major challenge for future research.